A family of circulant megastable chaotic oscillators, its application for the detection of a feeble signal and PID controller for time-delay systems by using chaotic SCA algorithm. (July 2021) - Rajagopal, Karthikeyan; Cimen, Murat Erhan; Jafari, Sajad; Singh, Jay Prakash; Roy, Binoy Krishna; Akmese, Omer Faruk; Akgul, Akif
Highlights: We are proposing a class of cyclic symmetry oscillators that has the megastable property with infinite coexisting attractors. Various dynamical properties of the proposed oscillators are discussed in detail. An application for the detection of a feeble signal by using the proposed circulant megastable oscillator is presented. Since chaotic oscillators are highly sensitive to a tiny change in the parameters or an external input to the oscillator, this property of the proposed oscillator is used for the detection of a feeble signal. Simulated results validate the effectiveness of the proposed application. A new chaotic sinus cosines algorithm (SCA) is developed using the randomness of megastable oscillators. Subsequently, this new chaotic sinus cosines algorithm is used to determine the PID controller parameter of time-delay systems concerning objective function. Abstract: Chaotic systems with cyclic symmetry are very rare and have been less discussed in the literature. Similarly, megastable oscillators, which can have a finite or infinite number of coexisting attractors, have also attracted researchers. We propose a class of cyclic symmetry oscillators with the megastable property with infinite coexisting attractors for the first time in the literature. Various dynamical properties of the proposed oscillators are discussed in detail. An application for the detection of a feeble signal by using the proposed circulant megastable oscillator is presented. Since chaotic oscillators are highly sensitive to a tiny change in the parameters or an external input to the oscillator, this property of the proposed oscillator is used for the detection of a feeble signal. Simulated results validate the effectiveness of the proposed application. After that, a new chaotic Sine-Cosine Algorithm (SCA) is developed using the randomness of megastable oscillators. Subsequently, this new chaotic sine-cosine algorithm is used to determine the PID controller parameters of time-delay systems concerning the objective function. As a result, the proposed chaotic sine-cosine algorithm presents better performance for time-delay systems when compared with the available algorithms in the literature.